Tissue culture for farmers : Participatory adaptation of low-input cassava propagation in Colombia - Escobar Pérez, Roosevelt H.; Hernández, C.M.; Larrahondo, N; Ospina, G.I.; Restrepo M., José M.; Muñoz Flórez, Ligia Carmenza; Tohme, Joseph M.; Roca, W. (Cambridge University Press, 2006)
The lack of good quality planting material of farmers' cassava varieties, produced locally and at low cost, is a major constraint limiting the expansion of cassava production in Colombia. This article describes the adaptation of conventional cassava propagation to a low-input scheme for rural tissue-culture multiplication, developed and run by small, resource-poor farmers (referred in this article as an informalfarmers' seed production system). Developed through a two-phase participatory process by a group of women farmers, a non-governmental organization and International Center for Tropical Agriculture scientists in a farmers' community in the hillsides of southern Colombia, the project resulted in alternative, economical and readily available sources of tissue-culture material and equipment. Rates of multiplication achieved with the system were as high as with conventional tissue-culture procedures.